The synthesis of chiral β-naphthyl-β-sulfanyl ketones via enantioselective sulfa-Michael reaction in the presence of a bifunctional cinchona/sulfonamide organocatalyst - Tözendemir, Deniz; Tanyeli, Cihangir (Beilstein Journal of Organic Chemistry, 2021)
Cinchona alkaloid-derived organocatalysts are widely employed in various asymmetric transformations, yielding products with high enantiopurity. In this respect, a bifunctional quinine-derived sulfonamide organocatalyst was developed to catalyze the asymmetric sulfa-Michael reaction of naphthalene-1-thiol with trans-chalcone derivatives. The target sulfa-Michael adducts were obtained with up to 96% ee under mild conditions and with a low (1 mol %) catalyst loading. Selected enantiomerically enriched sulfa-Michael addition products were subjected to oxidation to obtain the corresponding sulfones.
Keywords: asymmetric synthesis; bifunctional catalysis; cinchona alkaloids; organocatalysis; sulfa-Michael reaction